Lung involvement in patients with psoriatic arthritis - Mehmet Hünür,; Tahir Saygın Öğüt,; Ece Çelik,; Funda Erbasan,; Melis Dilbil,; Mine Nokay,; Mustafa Ender Terzioğlu,; Veli Yazisiz, (Archives of Rheumatology, 2024)
Objectives: The study aimed to describe the prevalence and patterns of pulmonary lesions in the patients with psoriatic arthritis (PsA). Patients and methods: Pulmonary symptoms and thorax imaging findings of 247 patients (155 females, 92 males, mean age: 52.0±12.6 years; range, 23 to 87 years) with PsA diagnosed according to CASPAR (Classification Criteria for Psoriatic Arthritis) diagnostic criteria were retrospectively reviewed between January 01, 2014 and December 31, 2020. Thoracic computed tomography or high-resolution computed tomography, whichever was accessible, was used as the imaging method. Results: Thoracic imaging revealed at least one pulmonary lesion in 25 (10.1%) patients. The frequency of interstitial lung diseases (ILD) was 3.6% (n=9) in the PsA cohort. Other commonly detected pulmonary lesions were pulmonary nodules (n=21, 8.5%) and airway abnormalities (n=15, 6.1%; eight emphysema and seven bronchitis). ILD patterns were nonspecific interstitial pneumonia in three (1.2%) patients, cryptogenic organizing pneumonia in two (0.8%) patients, and probable usual interstitial pneumonia in two (0.8%) patients. ILD patterns in two (0.8%) patients could not be categorized and accepted as unclassifiable type. None of the patients had apical fibrosis. The mean age was higher in patients with ILD (p=0.007), and ILD was found to be more common in males (p=0.010), current or former smokers (p=0.012), and patients receiving hydroxychloroquine treatment (p=0.028). Conclusion: The frequency and severity of ILD in the patients with PsA was lower than those reported in connective tissue diseases. Apical fibrosis, which may be present in ankylosing spondylitis, another member of the spondyloarthritis group, was not detected.